Gallbladder adenocarcinoma with upper abdominal pain: A case report. (November 2022) - Sampetoding, Samuel; Kusuma, Muhammad Ihwan; Pratiwi, Yulianti; Ulfandi, Devby; Faruk, Muhammad
Abstract: Introduction: The most prevalent malignancy of the biliary system and the fifth most common cancer of the gastrointestinal tract is gallbladder cancer. This cancer is extremely aggressive with a 19 % 5-year survival rate. Herein, we report a case of gallbladder cancer with an ambiguous symptom of upper abdominal pain. Presentation of case: A 51-year-old woman presented with abdominal pain persisting for 3 months. On examination, a lump on the right abdomen measuring 7 × 5 cm was found. Ultrasound showed a gallbladder mass measuring 8 cm, and magnetic resonance imaging showed an infiltrating gallbladder mass suggestive of segment VI liver malignancy. The patient underwent radical cholecystectomy with en bloc hepatectomy and lymph node dissection. Histopathology revealed poorly differentiated gallbladder adenocarcinoma that metastasized to the liver. The postoperative course was uneventful, and the patient was discharged on postoperative day 5. Discussion: In our case, we performed radical (extended or margin-clearing) cholecystectomy to remove the gallbladder with a margin of normal liver tissue along with regional lymphadenectomy. This procedure is used to improve staging and decrease the risk of recurrence. Conclusion: Although gallbladder cancer is rare in Indonesian populations, it has a high mortality rate because of the frequently advanced stage of the disease at the time of diagnosis. Radiography may determine its degree and malignancy features. Regardless of the tumor size, the prognosis of gallbladder cancer depends on its stage and removability. Highlights: Gallbladder cancer is a rare type of malignancy in Indonesian populations. The mortality rate is high owing to the frequently advanced stage at diagnosis. Radiography may determine the degree and malignancy features of the disease. Radical cholecystectomy removes the gallbladder with a margin of normal liver tissue. Regional lymphadenectomy improves staging and decreases recurrence.